Effect of the Type of Herbal Preparations (Powdered Plant Material vs. Dry Ethanolic Extracts) on the Bioaccessibility of Bearberry (Arctostaphylos uva-ursi (L.) Spreng.) Phytochemicals in Simulated Digestion Conditions - Łukasz Sęczyk; Danuta Sugier; Piotr Sugier (Molecules)
The main aim of this study was to determine the potential bioaccessibility of bearberry phytochemicals influenced by the type of herbal preparations. Herbal preparations–powdered plant materials and dry extracts obtained using various ethanol concentrations (0%, 20%, 40%, 60%, 80%, and 100%) were subjected to simulated gastric or gastrointestinal digestion for the evaluation of the bioaccessibility of the phytochemicals. The phytochemical characterization of the plant material, dry extracts, and potentially bioaccessible fractions was performed using high-performance liquid chromatography (HPLC) and spectrophotometric assays. The content of the main compounds, i.e., arbutin, hydroquinone, hyperoside, pentagalloylglucose, and picein, as well as the total phenolic content and in vitro antioxidant activity through the ABTS•+-scavenging activity and Fe3+-reducing power were determined. The bioaccessibility of arbutin, i.e., the main compound in bearberry, was high, in most cases exceeding 95%, and was generally unaffected by the experimental factors; however, the changes in the content of the other compounds, the total phenolic content, and the antioxidant activity were more prominent and influenced by the type of the herbal preparation and the stage of digestion. Given the compromise between the abundance of the bearberry phytochemicals, the antioxidant activity, and the resulting potential bioaccessibility of these phytochemicals, the dry extracts prepared with 40% ethanol seem to be the most promising for phytopharmaceutical purposes and functional food applications.